We Are the Land: Reflections on KXL Resistance at Rootz Camp. Issue 1 (2nd January 2023) - Keisch, Deborah; Scott, Tim
Abstract : This essay reflects on the efforts of a group of Lakota land and water protectors to resist the construction of the Keystone XL pipeline, within the larger context of the Indigenous sovereignty, land-back, and climate-justice movements across North America. These protectors articulate their struggles by speaking to what Leanne Simpson and others have referred to as a politics of Indigenous "radical resurgence" and by fighting violent and ongoing dispossession through attempts to reject a politics of recognition or sanction from the U.S. settler-colonialist state, an approach that embodies possibility through radical Indigenous thought and practice. The essay documents this antecapitalist epistemology by describing acts of resistance at Rootz Camp over a several-month period. The essay illustrates how such efforts go beyond simply resisting or existing outside of capitalism but rather seek to vision and build an alternative.